IMPACT OF DELAYED CURATIVE ONCOLOGICAL TREATMENT IN PATIENTS WITH PROSTATE CANCER DURING THE COVID-19 PANDEMIC: STUDY AT THE HOSPITAL DAS CLÍNICAS OF UFG (REMUNOM, 2025)
The COVID-19 pandemic has imposed serious challenges on the public health system, significantly impacting the diagnosis and treatment of chronic diseases, such as prostate cancer — the most common type among men. This study aims to analyze the effects of the pandemic on the delayed time between diagnosis and surgical treatment (radical prostatectomy) of patients treated at the Hospital das Clínicas of the Federal University of Goiás (HC-UFG), between 2018 and 2023. This is a cross-sectional, descriptive, population-based study, with data obtained from the public TabNet/DATASUS platform. The results reveal considerable delays in the years 2021 and 2022, with less than half of the patients being operated on up to six months after diagnosis in these periods. The analysis indicates that such delays may have compromised oncological outcomes, especially in high-risk patients, as evidenced by previous studies. It is understood that the pandemic has exacerbated the weaknesses of the public health system, reinforcing the urgency for strategies that ensure the continuity of oncological care during health crises.